The albedo loss from the melting of the Greenland ice sheet and the social cost of carbon - Sandra Gschnaller (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
I extend the reduced Greenland ice sheet (GIS) model-module of DICE-GIS (Nordhaus, 2019) by integrating snow-albedo feedback (SAF) and potential tipping of the ice sheet into the resuming DICE-GIS SAF model. This novel model extension allows to quantify the social cost of carbon (SCC) more precisely because the economic damages are not only related to intensified sea level rise, but also an accelerated increase in global temperature. Accounting for the SAF raises the SCC from 274.92 to 319.67 /tCO2 in 2100, an increase of 16.3%. The temperature increase is the key channel through which the SAF impacts the SCC.
Keywords: O13; Q15; Q58; 330; social cost of carbon; climate change; Greenland ice sheet; snow albedo feedback; tipping